Effects of hyperuricemia on perinatal outcome in hypertensive disorder of pregnancy - Hosna, Asma Ul; Bhuiyan, AKM Mohiuddin; E-Ferdous, Noor; Ahmed, Md Khurshed; Siddique, Md Abu; Salman, Mohammad; Begum, Sultana Razia; Rahman, Md Mukhlesur; Ahsan, Md Razib (University Heart Journal, 2009)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!--[if gte mso 10]> <![endif]--> The purpose of this study was to detect elevated uric acid level in maternal blood, presumably due to decrease renal urate excretion, for early detection of hypertensive disorder in pregnancy. This study showed that serum uric acid was significantly elevated in all cases of preeclampsia. The present study showed that serum uric acid levels were significantly elevated in eclampsia as compared with the levels in pregnancies complicated by hypertension (p < 0.05). The level of uric acid above 4.5 mg/dl is indicative of preeclamptic process and in such cases; the subjects deserve careful and close clinical follow up. Increasing higher concentration of uric acid i.e. 5.7 mg/dl, 6.3mg/dl, and 6.72mg/dl was observed in pregnancy with chronic hypertension, preeclampsia and eclampsia respectively. These results showed that serum uric acid could be used as a sensitive indicator of severity of preeclampsia. Out of 100 cases, there were 20 preterm baby and others such as stillbirth and IUD. So, these entire abnormal fetal outcomes were in the hyperuricaemic group and 5.37 times higher as compared to low serum uric acid group. Mean birth weight of preeclampsia and eclampsia were 2.31kg and 2.30kg respectively compared with 2.5kg in chronic hypertension group. Â Â  doi:10.3329/uhj.v4i2.2074 University Heart Journal Vol. 4 No. 2 July 2008 p.36-40